PROSES PEMBUATAN SILASE PENYEDIAAN HIJAUAN PAKAN TERNAK BERKUALITAS DAN KONTINU SEPANJANG TAHUN GUNA MENINGKATKAN PRODUKTIVITAS TERNAK RUMINANSIA DI NABIRE PAPUA - Mery C. Simanjuntak; Trijaya Gane Putra; Wardhana Wahyu Dharsono (Yayasan Education and Social Center, 2023)
Seeing the livestock population in the Nabire district of Papua, it is necessary to prepare the feed properly. Lack of feed during the dry season can be overcome by utilizing the abundance of feed during the rainy season. The strategy is to increase the shelf life of the forage that will be prepared as forage for use in the dry season by preserving the forage. One type of forage preservation is